2010
DOI: 10.1093/jmedent/47.4.639
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Francisella tularensis in Alaskan Mosquitoes (Diptera: Culicidae) and Assessment of a Laboratory Model for Transmission

Abstract: Tularemia is a zoonotic disease caused by the Category A bioterrorism agent Francisella tularensis. In Scandinavia, tularemia transmission by mosquitoes has been widely cited in the literature. We tested >2,500 mosquitoes captured in Alaska and found Francisella DNA in 30% of pooled samples. To examine the potential for transmission of Francisella by mosquitoes, we developed a mosquito model of Francisella infection. Larvae of Anopheles gambiae Giles and Aedes aegypti (L.) readily ingest F. tularensis but do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Considering recent reports of a high diversity of Francisella in environmental samples [9, 3032], these results indicate a restriction of Francisella diversity through persistence in mosquitoes. In line with this, F. novicida has been shown not to be transstadially maintained during mosquito development [33]. This suggests selectivity associated with the pathogenic F. tularensis subsp.…”
Section: Discussionmentioning
confidence: 74%
“…Considering recent reports of a high diversity of Francisella in environmental samples [9, 3032], these results indicate a restriction of Francisella diversity through persistence in mosquitoes. In line with this, F. novicida has been shown not to be transstadially maintained during mosquito development [33]. This suggests selectivity associated with the pathogenic F. tularensis subsp.…”
Section: Discussionmentioning
confidence: 74%
“…In a laboratory setting, F. tularensis is consistently recovered from deer flies for up to 5 days, but no longer than 14 days (Petersen et al, 2009). Similar to deer flies, the mosquito is not believed to support multiplication of F. tularensis (Triebenbach et al, 2010). A recent study indicated that Francisella DNA was detected in 30% of >2,500 mosquitoes captured in Alaska (Triebenbach et al, 2010).…”
Section: Pathophysiology Of Infection With F Tularensismentioning
confidence: 99%
“…Similar to deer flies, the mosquito is not believed to support multiplication of F. tularensis (Triebenbach et al, 2010). A recent study indicated that Francisella DNA was detected in 30% of >2,500 mosquitoes captured in Alaska (Triebenbach et al, 2010). However, F. tularensis was not transstadially transmitted in mosquitoes tested.…”
Section: Pathophysiology Of Infection With F Tularensismentioning
confidence: 99%
“…tularensis [18]. Mosquitoes have been tentatively classified as mechanical vectors of tularemia and are thought to only transmit this disease transiently [2, 19]. However, F .…”
Section: Introductionmentioning
confidence: 99%